SEARCH OF OPPORTUNITIES FOR THE DEVELOPMENT OF REHABILITATION SERVICES FOR CHILDREN WITH DISABILITIES - Petrochko, Zhanna; Slozanska, Hanna; Horishna, Nadiya (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article discusses the topical issue of finding opportunities for the development of rehabilitation services for children with disabilities. The research was carried out within the framework of the NFSU project “Research on the development of social rehabilitation services for children with disabilities and their families at the level of territorial communities in the war and post-war periods” (Competition “Science for the reconstruction of Ukraine in the war and post-war periods”; project number 2022.01/0166). The purpose of the article is to study the essence and experience of developing and implementing social services for children with disabilities within the framework of project activities at various levels. The tasks of the research are to analyze the research results of the needs and problems of supporting children with disabilities; to reveal the essence and types of rehabilitation services for children with disabilities based on the study of international documents and the legislation of Ukraine; to summarize information of the successful activities of international foundations/organizations and comprehensive of rehabilitation centers for supporting children with disabilities, providing them with high-quality social services. To achieve the goal and objectives of the article, theoretical methods (analysis, synthesis, systematization, comparison, generalization), analysis of regulatory documents regarding rehabilitation services for persons/children with disabilities, study of practical experience were used. The article characterizes the regulatory and legal basis for providing rehabilitation services to children with disabilities. An analysis of the latest publications on the research topic is made. The essence and principles of rehabilitation are revealed, the types of rehabilitation services are named, and their list is determined in accordance with the current legislation. A secondary analysis of the All-Ukrainian survey of parents and guardians of children with disabilities/persons with special needs (2023) was carried out in the context of the availability and desirability of social rehabilitation services. The results of project activities of various organizations in the direction of social support, implementation of social services for children with disabilities or training of specialists to provide such services are presented. The results of the activities of the IBO “Partnership “Every Child” within the framework of the World Bank project “Reformation of Institutional Care and Education of Children in Ternopil Region” are presented. The experience is revealed: the transformation of a child’s home into a center for the rehabilitation and development of a child through the implementation of various services; preparation of specifications for social services for children with disabilities and their families. The experience of implementation of the UNICEF project “Monitoring the needs and support of children in conditions of war” is also presented, namely: the experience of preparation and implementation of the Basic Program for improving the professional competence of medical and pedagogical specialists of childrens homes for training the personnel of institutions for the organization and provision of a complex of modern medical and social services, which would provide a holistic process of early detection, rehabilitation and development of the child based on partnership. The experience of providing rehabilitation services based on the Kyiv City Center for the Rehabilitation of Children with Disabilities is described.